Government Communication as Future-Making: Constructing Sociotechnical Imaginaries of Precision Medicine in Indonesia - Febby R. Widjayanto; Sidrotun Naim (Riviera Publishing, 2026)
Governmental communication has become an increasingly important arena through which states shape public expectations and legitimize emerging technologies. However, existing studies on sociotechnical imaginaries have predominantly focused on policy documents and institutional strategies, with comparatively limited attention given to official governmental communication during the formative stages of technological initiatives. This study examined how the Indonesian Ministry of Health constructed sociotechnical imaginaries of precision medicine through official news releases introducing the Biomedical and Genome Science Initiative (BGSi). Employing qualitative content analysis, this study analyzed the complete corpus of seven official news releases published between 2022 and 2025 during the formative communication stage of BGSi. The findings revealed that governmental communication constructed and legitimized a future-oriented vision of healthcare through four interconnected narratives: technoscientific governance, genomic datafication, technological sovereignty, and the strategic omission of ethical and participatory concerns. These findings demonstrated that official news releases functioned not merely as channels for policy dissemination but also as performative instruments through which governments anticipated, legitimized, and stabilized technological futures. This study contributed to the sociotechnical imaginaries literature by conceptualizing governmental communication as a formative site of sociotechnical future-making and extended empirical understanding of anticipatory governance and precision medicine communication in the Global South.